2024
DOI: 10.22270/ajdhs.v4i1.71
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pharmacists in Opioid Addiction Management

Pallav Dave

Abstract: Opioid addiction claims thousands of lives every year in the United States. The prevalence of misuse, abuse, and overdose continues to rise despite the measures and initiatives taken by the federal government and other government agencies to manage the problem. These efforts have led to a re-evaluation of the role different healthcare providers can play to ensure the problem is adequately addressed. Being one of the most accessible healthcare providers to patients under opioid therapy, pharmacists are better p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Research is emerging that AI presents greater opportunities for improved diagnosis more so in diseases such as cancer. 14,15 AI is important when it comes to examining large datasets which leads to greater accuracy and efficiency in diagnosis. 14 AI can also be used in breast cancer imaging with its accuracy being comparable to that of radiology.…”
Section: Benefits Of Digital Technologies In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…Research is emerging that AI presents greater opportunities for improved diagnosis more so in diseases such as cancer. 14,15 AI is important when it comes to examining large datasets which leads to greater accuracy and efficiency in diagnosis. 14 AI can also be used in breast cancer imaging with its accuracy being comparable to that of radiology.…”
Section: Benefits Of Digital Technologies In Healthcarementioning
confidence: 99%
“…14,15 AI is important when it comes to examining large datasets which leads to greater accuracy and efficiency in diagnosis. 14 AI can also be used in breast cancer imaging with its accuracy being comparable to that of radiology. 15 As such, digital technologies offer a lot of potential when it comes to improving the accuracy of medical diagnosis.…”
Section: Benefits Of Digital Technologies In Healthcarementioning
confidence: 99%
“…18 In type 1 diabetes mellitus, stress impact is influenced by dysregulated stress hormone regulation, insulin availability during stress, autonomic nervous system abnormalities, and individual psychological factors. 19…”
Section: Relationship Between Psychological Stress and Diabetes Prese...mentioning
confidence: 99%
“…Research has found that leading a sedentary lifestyle increases the risk of mental problems. 23,24,25 Lack of physical activity is always associated with poor mental well-being with individuals that have lower levels of exercise being known to lead to poor mental health outcomes. 26 When it comes to excessive use of social platforms, engaging in physical activity becomes a problem.…”
Section: Reasons Why Social Media Increases the Risk Of Mental Healthmentioning
confidence: 99%